Cone-Beam Computed Tomography-Based Spatial Prediction of Drug Dose After Transarterial Chemoembolization Using Radiopaque Drug-Eluting Beads in Woodchuck Hepatocellular Carcinoma. Issue 8 (4th August 2022) - Mikhail, Andrew S.; Pritchard, William F.; Negussie, Ayele H.; Inkiyad, Gazi; Long, Dilara J.; Mauda-Havakuk, Michal; Wakim, Paul G.; van der Sterren, William; Levy, Elliot B.; Lewis, Andrew L.; Karanian, John W.; Wood, Bradford J.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aims of this study were to develop a model to estimate drug dose delivered to tumors after transarterial chemoembolization (TACE) with radiopaque drug-eluting beads (DEBs) based on DEB density on cone-beam computed tomography (CT) and to evaluate drug penetration into tissue in a woodchuck hepatoma model. Materials and Methods: Transarterial chemoembolization was performed in woodchucks with hepatocellular carcinoma (N = 5) using DEBs (70–150 μm, LC Bead LUMI) loaded with doxorubicin. Livers were resected 45 minutes after embolization, immediately frozen, and cut using liver-specific, 3D-printed sectioning molds. Doxorubicin levels in tumor specimens were measured by high-performance liquid chromatography and correlated with DEB iodine content that was measured using prototype cone-beam CT-based embolization treatment planning software. Doxorubicin penetration into tissue surrounding DEBs was assessed by fluorescence microscopy of tumor sections. Fluorescence intensity was converted into doxorubicin concentration using calibration standards. Intensity-thresholded color heatmaps were generated representing extravascular drug penetration. Results: Consistent segmentation of DEBs on cone-beam CT was achieved using a semiautomated intensity thresholding method. A positive linear correlation (0.96) was found between DEB iodine content measured on cone-beam CT and the amount of doxorubicin measured in tumor specimens. Prediction of doxorubicin levels in tumor sections that were not included in model development was accurate, with a root-mean-square error of 0.08 mg of doxorubicin. Tumor penetration of eluted doxorubicin resulted in concentration gradients where drug content decreased with increasing distance from blood vessels containing DEBs. Drug penetration was greater for blood vessels containing DEB clusters compared with single DEB, with higher doxorubicin concentrations extending further away from the vessels. Conclusions: Estimation of drug dose delivered during transarterial chemoembolization in a woodchuck hepatocellular carcinoma model was possible using DEB radiopacity on cone-beam CT as a surrogate marker. Doxorubicin penetration was greatest adjacent to vessels containing DEB clusters compared with single DEB. Intraprocedural estimation of the spatial distribution of drug dose within the tumor could enable real-time adjustments to DEB delivery, to maximize treatment coverage or identify regions of tumor at risk for undertreatment.